Distal tibia interosseous osteochondroma with fibula deformity - Panta, Sunil; Thapa, Shrawan Kumar; Paudel, Krishna Prasad (Journal of Chitwan Medical College, 2021)
Osteochondroma, one of the commonest bone tumors, is a cartilage capped exostosis. It occurs commonly in rapidly growing ends of long bones. It’s rare in slowly growing regions of long bones. Osteochondroma present in distal tibial interosseous border causing fibular deformity is very uncommon. Osteochondroma is usually managed conservatively till the age of skeletal maturity, but distal tibial osteochondromas are managed surgically to prevent deformity, impending fibula fracture, ankle pain, syndesmotic injury irrespective of skeletal maturity. It is a case report of an 18-year-old male with gradually increasing, painless mass at the distal leg for 6 years, increasing bowing deformity since 2 years with no functional limitations. Clinical and radiological findings were consistent with distal tibial osteochondroma with deformity of the adjoining fibula. Exostosis was excised successfully leaving a thin deformed distal fibula. The result was painless, stable, and non-progressive residual ankle deformity. Histopathology confirmed the diagnosis with no malignant transformation.